Factors, and Impact of Bullying on Self-esteem and Interest of Senior Secondary School Science Students in North Central, Nigeria - Ojelade I.A; A.E.B, Ubom; S.O, Olamoyegun (Researchparks Publishing, 2025)
This study examined factors and impact of bullying on self-esteem, and interest of senior secondary school science students in North Central, Nigeria. The study used descriptive survey design. Population of the study was made up of all SSS science students in all the government senior secondary schools in North Central, Nigeria. The sample of the study was made of three hundred and eight four (384) students and teachers. Krejcie and Morgan table was use to select the sample size. This study employed the use of various questionnaires to collect information on all aspects of the study. The questionnaire was structured on a four-point type likert scale: Strongly Agreed, Agreed, Disagreed, Strongly Disagreed (SA, A, D, SD). The instrument was validated by my supervisors and another expert, who is an educationist. A test-retest reliability method was used to evaluate instrument stability, assessing temporal consistency, identify instrument bias, and establishing instrument validity. The reliability was measured using Chronbach’s alpha coefficient for calculation of internal consistency and was found to be 0.814. The time frame was good enough to measure the stability of the instrument. Mann-Whitney, and T-Test statistical analytical technique using SPSS Version 21 statistical package was used to analyze the data. The study revealed that male and female students have the same opinion on factors causing bullying, which are bully wants to gain dominance on others, jealousy and lack of empathy amongst others make students to become bullies. The opinions of male and female students on impacts of bullying on self-esteem was not different also which are bullying has made me feel worse about myself, the result also revealed that bullying has serious negative effect on academic performance of the bullied. Based on the findings, the following are measures that need to be put in place by the stakeholders in education in other to curb bullying among senior secondary school science students in North Central, Nigeria: develop and implement anti-bullying policies; establish a bullying reporting system; create a safe and supportive school climate that fosters open communication among students, teachers and parents and provide teacher training on bullying prevention and response and assign classroom mentors and advisors.